A profile of mental health and behaviour in Prader–Willi syndrome. Issue 2 (17th December 2019) - Feighan, S.‐M.; Hughes, M.; Maunder, K.; Roche, E.; Gallagher, L.
Abstract: Background: Prader–Willi syndrome (PWS) is a neurogenetic syndrome with an associated behavioural phenotype and a high incidence of behaviours of concern and psychiatric co‐morbidity. These associated behaviours and co‐morbidities are not well addressed by existing interventions, and they impact significantly on affected individuals and their caregivers. Methods: We undertook a national survey of the needs of individuals with PWS and their families in Ireland. In this paper, we report on the parent/caregiver‐reported mental health, behavioural and access to services. Results: Over 50% of individuals with PWS in this survey had at least one reported psychiatric diagnosis, the most common diagnosis was anxiety. The most commonly reported behaviours in children were skin picking, repetitive questioning, difficulty transitioning and non‐compliance. The same four behaviours were reported by caregivers as being the most commonly occurring in adolescents and adults in addition to food‐seeking behaviours. Increased needs for mental health services were also reported by caregivers. Individuals with PWS had an average wait of 22 months for an appointment with a psychologist and 4 months for an appointment with a psychiatrist. Conclusion: This study highlighted high levels of psychiatric co‐morbidities and behavioural concerns in individuals with PWS in Ireland. The findings of this study suggest that there is an urgent need to provide specialist psychiatric and behavioural interventions to manage complex mental health and behavioural needs to better support individuals with PWS and reduce caregiver burden.